Innovative Leadership as Enabling Function Within Organizations: A Complex Adaptive System Approach. Issue 3 (December 2015) - Elkington, Rob; Booysen, Lize
Abstract : Innovation is vital for organizational thriving in the complex reality of the 21st century. Leadership that flourished in stable environments may need to adapt to support thriving in a new globalized era. What does this type of leadership look like, and how does it function? The current article suggests that such an adaptation may be best expressed through leadership "as enabling function" within the organization as a complex adaptive system.